The future of the financial exchanges insights and analysis from the Mondo Visione Exchange Forum - Skeete, Herbert C. (Burlington, MA : MondoVisione/Elsevier, 2009)
In May 2007, an extraordinary meeting took place in London. The Exchange Forum. Chief executives from many of the world?s most important financial exchanges came together with senior executives from a wide array of global banking, trading, and investing firms, index providers, regulators, system suppliers, and key academics to discuss the rapidly changing business and technological environment in which exchanges function. The forum was an exclusive event, open only to the most senior-level individuals in the global exchanges community: those who run exchanges, who are clients of exchanges, who invest in exchanges, and who supply goods and services to exchanges. In presentations and panel discussions over two days, these experts explored the effect of shrinking margins as more instruments became exchange traded rather than OTC and the conflicts that creates. They shared what exchanges are doing today to respond to the challenges wrought by competition, globalization, and rapid technology advances. And they looked into the future and discussed the multi-asset, multi-currency, and multi-region trading that holds out the promise of future success. The book is based on the discussion and analysis that took place at this exclusive event that brought together leading exchange professionals, their customers, and suppliers from around the globe to share insights and experiences. It will provide an overview of the latest technological, regulatory, and market developments in the exchange industry and the common problems exchanges face; explain how these problems are being addressed; and present the consensus view ? from leading exchange professionals ? about how to move forward. Most significant, the ideas in the book will come directly from the world?s leading exchange professionals and customers. Hear the voices of executive-level exchange professionals throughout the book for a candid, realistic, and high-level analysis of the exchange business, its present and future. Share the stories of success and failure these exchange executives shared as they discussed solutions to common challenges. Chart the way forward for your exchange business with confidence based on the collective insights and experience of these professionals.
Sections: I. A Relentless Pace of Change; II. Demutualization; III. The Next Set of Challenges; IV. New Possibilities.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Foreign exchange -- Forecasting; Electronic books